Answer on Mechanics | Relativity Question for asif rafiq
x²+y²=4 ==> y(x) = √(4-x²).
Now we can find derivative of y(x) with respect to x:
y'(x) = (1/2)*(4-x²)^(-1/2)*(-2x) = -x(4-x²)^(-1/2).
So, when x is equal to √2 (and so does y)
y'(√2) = -√2(4-(√2)²)^(-1/2) = -√2*2^(-1/2) = -√2*(1/√2) = -1.
Therefore, y is changing with the rate of -1 with respect to x when the satellite is at the point (√2,√2).
Need a fast expert's response?Submit order
and get a quick answer at the best price
for any assignment or question with DETAILED EXPLANATIONS!